Review: Gene of 16S rRNA is the gold standard to diagnose bacteria (World Journal of Current Medical and Pharmaceutical Research, 2023)
The success of the biochemical tests depends on the purity of the culture, and this requires special preparations for obtaining, transporting and purifying of sample, use of selective media, duration of incubation, temperatures and others and all this takes time and effort.It may require sending slow-growing pathogens to laboratories that provide the requirements for their growth, but they may be far from the source of their collection, and thus it takes a long time to diagnose pathogen. Also, biochemical tests reflect the activity of the gene responsible for the production of a particular substance, and this gene may be present, but it does not work, and therefore the result may be a misdiagnosis. Gene of 16S rRNA is found in all bacteria, and it contains stable regions through which bacteria can be identified, and other variable regions through which bacterial species can be distinguished. As well as, diagnosis of 16S rRNA gene does not require the requirements that are required by biochemical tests for the diagnosis of bacteria, and mutations that occur in this gene do not affect its basic function, which is diagnosis, so 16S rRNA gene is the gold standard for bacterial diagnosis. In principle, it is possible to rely on phenotypic characteristics to diagnose bacteria, but confirmatory diagnosis and registration of new species is done through 16S rRNA gene using polymerase chain reaction.